Analisis Perbandingan Konsumsi Daya Library Image loader pada Android (Studi Kasus: Aplikasi Media Sosial) - Muhammad Abyan Safitra; Mahardeka Tri Ananta; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The battery power of the smartphone can not keep pace with other technological advances in improving performance such as CPU and memory, so research needs to be done in order to develop mobile apps that have low power consumption levels. According the survey, from the many existing mobile apps, media sosial apps are the most used apps by smartphone users. One way to develop mobile applications that can have low power consumption is to optimize library usage. Library Image loader is one of the most popular android libraries used in media sosial applications to handle image transformation. Library Image loader which will be tested in this research is library Picasso, Universal image loader (UIL) and Glide. The research is done by making a media sosial prototype application that resembles instagram timeline that will be used as a dummy system. The test will be performed over a specified time range and by using several different image size parameters to see the effect of image size differences on the power level of the Library Image loader. The results showed that the Glide library had the lowest average power consumption of 225,780 mW. While for testing with different image sizes, it only affects the Picasso and UIL libraries, that is the larger the image size, the greater the average power consumption level required.